Lathrolestes pleuralis Thomson 1883 ... - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes pleuralis (Thomson, 1883) Figs. 104–105. Lathrolestus pleuralis Thomson, 1883: 916 –917. Lectotype ♀, MZLU [examined]. Type locality: Sweden (Norrland). Material. 1♀ 1♂, DENMARK, ZMUC; 1♀, NORWAY, Akershus, Ullensaker, Sessvollmoen, Aurtjernet W, 26.VI–25.VIII.2007, leg. L. O. Hansen, ZMUN; 1♀, SWEDEN, Gästrikland, NHRS; 4♀, SWEDEN, Lappland, Sorsele kommun, Ammarnäs, Vindelfjällens naturreservat, Tjulträsklaspen, Alpine birch wood. N65°58.007, E16°03.630 (=TrapID 46) 26.vii–15.viii.2004 (=coll. event ID 1201), leg. SMTP, NHRS; 2♀, SWEDEN, Uppland, Älvkarleby kommun, Båtfors. Pine forest w. blueberry. N60°27.639´E17°19.069´(=Trap ID 7), 17.vi–03.vii.2003 (=coll. event ID 378), leg. SMTP, NHRS; 1♀, SWITZERLAND, NHRS-HEVA000002033, NHRS. Diagnosis. This species differs from other species of the genus by the following character states: 1) clypeus projecting distinctly anteriorly, but not strongly, and not incurved, 2) head narrowed behind eyes, 3) occipital carina incomplete dorsally, 4) areolet ... : Published as part of Reshchikov, Alexey, 2015, Review of North European species of the genus Lathrolestes (Hymenoptera, Ichneumonidae) with description of one new species from Öland (Sweden), pp. 1-47 in Zootaxa 4033 (1) on page 36, DOI: 10.11646/zootaxa.4033.1.1, http://zenodo.org/record/289776 ...